The effects of herbal plant extracts on the growth and sporulation of Colletotrhichum gloesporioides - Johnny, Lucy; Yusuf, Umi Kalsom; Nulit, Rosimah (FACT Limited, 2010)
Objectives: The antifungal activities of the leaf extracts of fifteen selected medicinal plants; Alpinia galanga L., Alstonia spatulata Blume., Annona muricata L., Blechnum orientale L., Blumea balsamifera L., Centella asiatica L., Dicranopteris linearis, Dillenia suffruticosa, Litsea garciae Vidal., Melastoma malabathricum L.,Momordica charantia L., Nephrolepis biserrata (Sw.)., Pangium edule Reinw., Piper betle L., and Polygonum minus Huds., were evaluated on the plant pathogenic fungus; C.loeosporioides isolated from mango.